RF discharge for in situ mirror surface recovery in ITER. (17th August 2015) - Razdobarin, A.G.; Dmitriev, A.M.; Bazhenov, A.N.; Bukreev, I.M.; Kochergin, M.M.; Koval, A.N.; Kurskiev, G.S.; Litvinov, A.E.; Masyukevich, S.V.; Mukhin, E.E.; Samsonov, D.S.; Semenov, V.V.; et al.
Abstract: Almost all optical diagnostic systems in ITER will require the implementation of mirror recovery and protection systems. Plasma cleaning is considered to be the most promising technique for the removal of metal deposits from optical surfaces. The engineering and physical aspects of RF discharge application for continuous or periodic plasma treatment are discussed with a focus on implementation under ITER conditions. The ion flux parameters obtained in capacitively coupled (CC) RF discharge were measured in the mock-up of a plasma cleaning system. The uniformity of sputtering in CC RF discharge with and without a magnetic field was studied experimentally for the cylindrical discharge reactor geometry and compared with numerical simulations. The sharp increase in the sputtering rate resulting from the non-uniform radial distribution of the ion flux was observed near the electrode edges. The longitudinal magnetic field improves sputtering uniformity. It was demonstrated that Al/Al2 O3 deposits can be removed in the Ne and D2 plasma of CC RF discharge but long-term exposition results in the degradation of the polycrystalline molybdenum mirror surface. The efficiency of Al sputtering in the atmosphere containing O2 and N2 fractions was studied in the D2 /O2 and D2 /N2 plasma of glow discharge. The addition of 2% of oxygen or nitrogen increases the sputtering yield by 3–4 times as compared with that in a nominally pure D2 discharge. The impact of metal deposits on the performance of diagnostic mirrors is discussed. It was shown that an ultrathin metallic film with a thickness as low as a few nm may cause a significant degradation of diagnostic mirrors with a transparent coating.